Kepercayaan Konsumen sebagai Mediator: Menghubungkan Influencer dan Kualitas Produk dengan Niat Beli di TikTok - Tato Priyo Sulistiyono; Muhammad Rexsa Assyarofi (CV. Ulil Albab Corp, 2024)
This study aims to analyze the influence of product quality and influencers on consumer trust and its impact on purchase intention. Data was collected through a quantitative approach through a survey involving respondents who actively use the TikTok platform. The sample used was 200 respondents. Data analysis was carried out using Path analysis through the Smart PLS application. The results showed that product quality positively and significantly influences consumer trust, which in turn impacts purchase intention. In contrast, the presence of influencers only considerably influences consumer trust. The findings indicate that companies must improve product quality and build consumer trust as critical strategies to increase purchase intention. This research provides important insights for companies in formulating more effective marketing strategies in the digital era, especially on the TikTok platform.